2015
DOI: 10.1093/biostatistics/kxv048
|View full text |Cite
|
Sign up to set email alerts
|

Spatial measurement error and correction by spatial SIMEX in linear regression models when using predicted air pollution exposures

Abstract: SUMMARYSpatial modeling of air pollution exposures is widespread in air pollution epidemiology research as a way to improve exposure assessment. However, there are key sources of exposure model uncertainty when air pollution is modeled, including estimation error and model misspecification. We examine the use of predicted air pollution levels in linear health effect models under a measurement error framework. For the prediction of air pollution exposures, we consider a universal Kriging framework, which may in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…In an analysis of a Massachusetts birth cohort from 2008, Alexeeff et al found that a 1 μg/m 3 difference in ambient PM 2.5 exposure during the third trimester was associated with 3.5 g lower birth weight. 7 This difference increased in magnitude to 4.9 g lower birth weight when they applied their spatial simulation extrapolation measurement error correction method. Unlike our approach, they corrected exposures estimated from averages of independent monthly spatial exposure models instead of correcting predictions from a spatiotemporal model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an analysis of a Massachusetts birth cohort from 2008, Alexeeff et al found that a 1 μg/m 3 difference in ambient PM 2.5 exposure during the third trimester was associated with 3.5 g lower birth weight. 7 This difference increased in magnitude to 4.9 g lower birth weight when they applied their spatial simulation extrapolation measurement error correction method. Unlike our approach, they corrected exposures estimated from averages of independent monthly spatial exposure models instead of correcting predictions from a spatiotemporal model.…”
Section: Discussionmentioning
confidence: 99%
“…If the exposure surface is assumed to be random with fixed monitor and cohort locations, such as in the classical formulation of kriging problems, 12 then a parametric bootstrap, or a similar approximate procedure, can be used to correctly remove bias and adjust standard errors. 2 A second approach to measurement error correction under this paradigm is the spatial simulation extrapolation method developed by Alexeeff et al , 7 which introduces additional measurement error into simulated datasets and then calculates a back-transformed value that corresponds to no measurement error.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…80 To date, studies have not used regression calibration methods to correct for non-differential EDC exposure misclassification, but studies of air pollutants have successfully used these methods to study a variety of health effects while accounting for exposure measurement error. 208 …”
Section: Challenges To Making Stronger Inferences About Edcs and Chilmentioning
confidence: 99%
“…More recently, Huque et al demonstrated that the expected amount of bias depends on the correlation between exposure and the random error from the regression model, and proposed parametric (64) and semiparametric (65) approaches to address this bias. Other recent work has addressed such spatial misalignment between measurements of exposures, covariates, and health outcomes using a variety of methods, including corrections in two-stage exposure models (66), SIMEX (67), and likelihood-based approaches (68). …”
Section: Accounting For Measurement Errormentioning
confidence: 99%